Misclassification of acute respiratory distress syndrome after traumatic injury: The cost of less rigorous approaches. Issue 3 (September 2015) - Hendrickson, Carolyn M.; Dobbins, Sarah; Redick, Brittney J.; Greenberg, Molly D.; Calfee, Carolyn S.; Cohen, Mitchell Jay
Abstract : BACKGROUND: Adherence to rigorous research protocols for identifying adult respiratory distress syndrome (ARDS) after trauma is variable. To examine how misclassification of ARDS may bias observational studies in trauma populations, we evaluated the agreement of two methods for adjudicating ARDS after trauma: the current gold standard, direct review of chest radiographs and review of dictated radiology reports, a commonly used alternative. METHODS: This nested cohort study included 123 mechanically ventilated patients between 2005 and 2008, with at least one PaO2 /FIO2 less than 300 within the first 8 days of admission. Two blinded physician investigators adjudicated ARDS by two methods. The investigators directly reviewed all chest radiographs to evaluate for bilateral infiltrates. Several months later, blinded to their previous assessments, they adjudicated ARDS using a standardized rubric to classify radiology reports. A κ statistics was calculated. Regression analyses quantified the association between established risk factors as well as important clinical outcomes and ARDS determined by the aforementioned methods as well as hypoxemia as a surrogate marker. RESULTS: The κ was 0.47 for the observed agreement between ARDS adjudicated by direct review of chest radiographs and ARDS adjudicated by review of radiology reports. Both the magnitude and direction of bias on the estimates of association between ARDS and established risk factors as well as clinical outcomes varied by method of adjudication. CONCLUSION: Classification of ARDS by review of dictated radiology reports had only moderate agreement with the current gold standard, ARDS adjudicated by direct review of chest radiographs. While the misclassification of ARDS had varied effects on the estimates of associations with established risk factors, it tended to weaken the association of ARDS with important clinical outcomes. A standardized approach to ARDS adjudication after trauma by direct review of chest radiographs will minimize misclassification bias in future observational studies. LEVEL OF EVIDENCE: Diagnostic study, level II.